Management of dactylitis in patients with psoriatic arthritis: an updated literature review informing the 2021 GRAPPA treatment recommendations - Palominos, PE; Fernández-Ávila, DG; Coates, LC; Adebajo, A; Toukap, AN; Abogamal, A; Polachek, A; van Kuijk, AWR; Caso, F; de Marco, G; Kaeley, GS; Steinkoenig, I; et al. (Journal of Rheumatology, 2022)
Objective This literature review aimed to identify the most efficacious current interventions for dactylitis and provide up-to-date scientific evidence to support the 2021 Group for Research and Assessment of Psoriasis and Psoriatic Arthritis (GRAPPA) recommendations on the management of psoriatic arthritis.